ANALISIS PENGARUH PARTISIPASI DAN PERAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN YALIMO - Estepanus Lolo Kassa; Meinarni Asnawi; Bill Pangayouw (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2019)
The purpose of the study is those the role of participation and information systems in regional financial management on the performance of regional governments. The Data Analysis Method uses an econometric approach in formulating estimated effects between variables through OLS.  While the mean score of the sub-indicators uses Quantitative Descriptive. Research results show: (1) Participation in the preparation of the APBD, shows a pattern of positive relations between the level of participation and the public presentation of local governments.  So that participation is an important and a dominant aspect capable of encouraging the performance of local government, (2) Regional Financial Management Information System, is a form of cutting down the bureaucratic flow in the technical management of regional finance, this research encourages the public presentation of regional government from regional financial aspects. Influence of 38 percent, (3) participation in the preparation of APBD and technical management of regional finance using the SIKD system, will positively support the increase in local government performance by 85.9 percent.